Current anti-biofilm strategies and potential of antioxidants in biofilm control. Issue 11 (2nd November 2018) - Ong, Kuan Shion; Mawang, Christina Injan; Daniel-Jambun, Delhousie; Lim, Yau Yan; Lee, Sui Mae
ABSTRACT: Introduction : Biofilm formation is a strategy for microorganisms to adapt and survive in hostile environments. Microorganisms that are able to produce biofilms are currently recognized as a threat to human health. Areas covered : Many strategies have been employed to eradicate biofilms, but several drawbacks from these methods had subsequently raised concerns on the need for alternative approaches to effectively prevent biofilm formation. One of the main mechanisms that drives a microorganism to transit from a planktonic to a biofilm-sessile state, is oxidative stress. Chemical agents that could target oxidative stress regulators, for instance antioxidants, could therefore be used to treat biofilm-associated infections. Expert commentary : The focus of this review is to summarize the function and limitation of the current anti-biofilm strategies and will propose the use of antioxidants as an alternative method to treat, prevent and eradicate biofilms. Studies have shown that water-soluble and lipid-soluble antioxidants can reduce and prevent biofilm formation, by influencing the expression of genes associated with oxidative stress. Further in vivo work should be conducted to ensure the efficacy of these antioxidants in a biological environment. Nevertheless, antioxidants are promising anti-biofilm agents, and thus is a potential solution for biofilm-associated infections in the future.